Preparação de novos compósitos suportados em matriz de fibra vegetal/natural. - Esmeraldo, Milena Alencar (2006)
In recent years there was a rapid development in the field of composites reinforced by natural fibers like (jute, sisal, coir, hemp etc). Natural fibers are an important alternative, offering several advantages such their abundant, biodegrability, light weight, renewability, are not toxic, presents low cost application compared with synthetic fibers and may be easily modified by chemical treatment. The present work aimed the study, preparation and characterization of composites of phenolic resin (matriz) based on CNSL, reinforced by natural fibers of coir and jute. Superficial modification on the fibers were carried out through alkali treatment (mercerization) NaOH 5% and NaOH 10% (75 0C) and bleaching with sodium hipoclorite (NaClO/H20 1:1) (60 0C). All the fibers composites were prepared by open mold. The composites and fibers were characterized by analysis techniques such mechanical tensile strength (elongation at break, young’s modulus, resistant at break); TG/DTG (Thermogravimetry); DSC (Differential Scanning Calorimetric); DRX (Difractrogram X - Ray); dielectric properties (Dielectric Conductivity, Dielectric Loss) and SEM (Scanning Electron Microscopy) investigation on the surface modification in fibers and composites after chemical treatment. The results to coir and jute fibers composites showed an increase of mechanical properties. The best mechanical performance was generally obtained for composites of jute and coir after NaOH 5% and NaOH 10% showing an enhancement of mechanical properties resistant at break (28%) and (48%) respectively. IV The thermal degradation behavior of composites and coir - jute fibers under a nitrogen atmosphere showed an increase of thermal stability after alkaline treatment NaOH 5% e 10 % compared with untreated fibers. To jute fibers it was observed an improvement of (218-228 0C) to coir fibers this increased it was (259- 276 0C). The same thermal stability was evaluated to composites of theses fibers after alkaline treatment NaOH 5% and NaOH 10%. To jute fibers composites the best results were (302-3060C) while coir composites were (288-310 0C). From the results obtained, it is possible to conclude that alkaline treatment contribute to significant improvement of thermal behaviour of the composites The SEM investigation showed significant improvement on surfaces of jute and coir fibers after chemical treatment. The alkali treatment, removed non-celluloic components from fibers surface, expoding their internal fibrillar structure. As a consequence the treatment promoted an increase on interfacial adhesion between coir and jute fibers reinforced phenolic resin composite